Análisis de un documento de extirpación de idolatrías procedente del complejo arqueológico Lumbra, valle medio del río Chancay-Huaral - Van Dalen Luna, Pieter (2010)
It details the discovery of an early colonial document, for a ceremony to extirpate idolatry, from an archaeological excavation unit on the raised platform of Sector B, the Archaeological Complex of Lumbra in 2008. This archaeological findings allows us to have information about the context and how these ceremonies were developed in the archbishopric of Lima.